O ensino da língua espanhola no Brasil: um olhar para aspectos da constituição identitária do professor de espanhol - Sales, Quênia Côrtes dos Santos (2007)
This dissertation aims at inquiring some aspects of the identitary constitution of the Spanish teacher as a foreign language without graduation in the field of foreign language teaching. This research uses some concepts from the French Discourse Analysis influenced by the Lacanian psychoanalysis. In such a perspective, we consider that the subject is constituted in and by the language. The corpus is composed by Spanish teachers sayings about their own experiences in the learning and in the teaching of Spanish. The analysis of these sayings shows that these teachers constitute themselves as foreign language teachers in the gap between the discourse of necessity, which has been spread over since people s interests in learning Spanish have increased in Brazil, and the discourse of the effort, which allows the teachers accomplish the demands of the market, assuming the position of a Spanish teacher.